The External History of Judiciary between Bourdieu and Foucault - Brindisi, Gianvito (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
This paper aims to investigate the relationship between the law and its outside, reactivating the concept of external history of law intended as history of judiciary. It tries to carry to extremes the declination of external history of law that is suggested in an essay by Maurice Hauriou and the history of justice that is recently proposed by Pietro Costa, and it shows how it is possible to achieve this goal by analyzing the judicial practices through the genealogy of Michel Foucault and the historical sociology of Pierre Bourdieu. Both of them practice a form of problematization of justice, overcome the division between subjectivism and objectivism and carry out an external history of justice in relation to the processes of subjectivation. By means of a structured comparison between genealogy and historical sociology, we propose an external history of judiciary meant as history of the articulation of heterogeneous fields of normativity. Parole chiave: External History of Law; Genealogy; Historical Sociology; Fields of Normativity; Jurisprudence Indice: 1. Il diritto, la giustizia e il loro fuori – 2. Affinità metodologiche – 3. L’analisi della giustizia – 4. Giustizia, potere e soggettività tra campo e rete – 5. Campo o rete medico-legale? – 6. Complementarità delle analisi